A Floristic–ecological classification of gorse scrub communities with Echinospartum ibericum (Fabaceae) in the Iberian Peninsula - Pulgar Sañudo, Íñigo; Herrera Rodríguez, José Manuel (Mediterranean Botany, 2026)
We analysed 194 phytosociological relevés from Echinospartum ibericum scrub communities across the Iberian Peninsula. Classification and ordination of the relevés were performed using multivariate statistical analyses, yielding 13 groups comprising nine syntaxa (associations or subassociations), three variants, and one transitional unit. For each community, we documented the distribution, bioclimatic characteristics, diagnostic species, and phytosociological class affinities of the participating flora. Relevés taken at higher altitudes were enriched in species of the class Junipero-Pinetea, whereas those from lower altitudes were enriched in species of the class Cytisetea. However, of the 12 communities identified, Cytisetea species predominated in eight, Festucetea in two, Calluno-Ulicetea in one, and Junipero-Pinetea in one. A syntaxonomic scheme is presented in accordance with these results.